2020
DOI: 10.3389/fpls.2019.01783
|View full text |Cite
|
Sign up to set email alerts
|

Pores for Thought: Can Genetic Manipulation of Stomatal Density Protect Future Rice Yields?

Abstract: Rice (Oryza sativa L.) contributes to the diets of around 3.5 billion people every day and is consumed more than any other plant. Alarmingly, climate predictions suggest that the frequency of severe drought and high-temperature events will increase, and this is set to threaten the global rice supply. In this review, we consider whether water or heat stresses in cropsespecially ricecould be mitigated through alterations to stomata; minute pores on the plant epidermis that permit carbon acquisition and regulate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 114 publications
(232 reference statements)
3
27
0
1
Order By: Relevance
“…Ectopic overexpression of RR22 also resulted in a decrease in the number of adjacent stomatal cell files. This effect on stomata development may involve the genes SHR and SCR, because these partner transcription factors positively regulate the formation of stomatal cell files in rice (Schuler et al, 2018;Buckley et al, 2019;Wu et al, 2019) and, based on studies in Arabidopsis, cytokinin can inhibit SCR expression (Zhang et al, 2013). These results suggest that, in addition to affecting cell size and proliferation, that alterations in the cytokinin transcriptional response can also affect the developmental architecture of the rice leaf.…”
Section: Discussionmentioning
confidence: 93%
“…Ectopic overexpression of RR22 also resulted in a decrease in the number of adjacent stomatal cell files. This effect on stomata development may involve the genes SHR and SCR, because these partner transcription factors positively regulate the formation of stomatal cell files in rice (Schuler et al, 2018;Buckley et al, 2019;Wu et al, 2019) and, based on studies in Arabidopsis, cytokinin can inhibit SCR expression (Zhang et al, 2013). These results suggest that, in addition to affecting cell size and proliferation, that alterations in the cytokinin transcriptional response can also affect the developmental architecture of the rice leaf.…”
Section: Discussionmentioning
confidence: 93%
“…Although global climatic variability is a serious threat to food security, genetic engineering of stomatal development will enable us to create stress-tolerant crops (Serna and Fenoll, 2002;Korres et al, 2017). By controlling stomatal development and reducing stomatal density, rice can control water loss and make it easier to survive under drought conditions (Buckley et al, 2019). The lack of RSD1 led to a reduction of stomatal density and the leaf water loss rate in rice.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of RSD1 led to a reduction of stomatal density and the leaf water loss rate in rice. The effect of stomatal density on plants has been applied to create drought-resistant crops (Buckley et al, 2019). Recent research has shown that excessive expression of EPF genes in wheat and rice can significantly improve water use efficiency without affecting plant yield when stomatal density is reduced (Caine et al, 2019;Dunn et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Reducing stomata density can help restricting water loss; however, it also reduces leaf CO 2 levels by hindering CO 2 exchange between the plant and the environment [ 18 ]. A recent study implied developing future-ready water-use efficient rice by targeting stomatal density using epidermal patterning factor OsEPF1.…”
Section: Transgenic Approach For Improving Rice Drought Tolerancementioning
confidence: 99%